Adherence to NCCN screening guidelines for germline testing of patients with pancreatic cancer at a large academic medical center: A retrospective chart review. Issue 28 (1st October 2022) - Rosso, Claudia; Devico Marciano, Naomie; Nathan, Deepika; Chen, Wen-Pin; Dayyani, Farshid; Zell, Jason; McLaren, Christine E.; Osann, Kathryn; Flodman, Pamela; Valerin, Jennifer Brooke
Abstract : 342 Background: Pancreatic ductal adenocarcinoma (PDAC) carries a poor prognosis with an overall 5-year survival rate of 10%. Depending on geographic region, 10-20% of cases are hereditary, with mutations in BRCA1 and BRCA2 being the most common. Contrary to popular belief, clinical risk factors such as family history of cancer and young age of onset are not reliable predictors for which patients may carry one of these predisposing mutations. In 2018, the National Comprehensive Cancer Network (NCCN) recommended that all pancreatic cancer patients should receive germline testing, regardless of family history. In a compliance analysis, we hypothesized that patients diagnosed after the NCCN guideline changes were more likely to be referred for genetic testing than those diagnosed beforehand. Methods: We conducted a retrospective chart review to compare trends in genetic testing of PDAC patients diagnosed from 02/17 - 07/18 versus 08/18 - 01/20, pre- and post-changes to NCCN guidelines, respectively.Family and personal cancer history, referral patterns and results of genetic counseling (GC) were recorded. Data were compared using Chi-square, Fisher's Exact, and multivariate analyses. Results: There were 268 patients treated for PDAC (128 pre-, 140 post-) at a large academic institution. Demographics across both groups were comparable. A total of 175 were seen by our institution's medical oncologist (84 pre-, 91 post-). Overall, 52 were referred to GC, 32 attended, 12 at our institution. More PDAC patients were referred to GC following the guideline changes (21% vs. 47%, p = 0.0005, Table). Patients with a family history of cancer were more likely to be referred to genetic testing (51% vs. 19%, p = 0.0002). This was the case for both pre- (odds ratio (OR) = 15.217 (95% CI, 2.725, 286.663)) and post- (OR = 3.353, (95% CI 1.263, 9.435)) eras, but the effect was not statistically significant when compared between eras ( p = 0.2034). Of all patients who underwent genetic testing, 27% were found to have a deleterious germline mutation related to hereditary PDAC. Conclusions: Despite a significant increase in referrals of PDAC patients for genetic testing following the guideline changes, adherence remains inconsistent with more than half of patients still not being referred. As a limitation of this study, we were not able to capture if patients were referred for GC outside of our network. Historically, the medical oncologist places the referral. However, as a possible solution to improve guideline adherence, referral for genetic testing could be initiated after initial diagnosis of PDAC by any provider, regardless of their role on the healthcare team.GC referral patterns, unknowns excluded. Referred Attended Completed Mutation positive Pre 15/73 (21%) 6/8 (75%) 6/6 (100%) 2/5 (40%) Post 37/78 (47%) 26/29 (90%) 22/24 (92%) 5/21 (24%) p- value 0.0005 0.2917 0.9999 0.5875